2023
DOI: 10.1098/rstb.2022.0147
|View full text |Cite
|
Sign up to set email alerts
|

Beak shape and nest material use in birds

Catherine Sheard,
Sally E. Street,
Caitlin Evans
et al.

Abstract: The evolution of behaviour can both influence, and be influenced by, morphology. Recent advances in methods and data availability have facilitated broad-scale investigations of physical form and behavioural function in many contexts, but the relationship between animal morphology and object manipulation—particularly objects used in construction—remains largely unknown. Here, we employ a new global database of nest materials used by 5924 species of birds together with phylogenetically informed random forest mod… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
7
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 16 publications
(10 citation statements)
references
References 69 publications
0
7
0
Order By: Relevance
“…Avian cranial morphology is usually associated with diet in birds, especially the beak (Soons et al 2015), though this may be constrained genetically (Bright et al 2016;Tokita et al 2017). Bird beaks are important for other functions including thermoregulation (Greenberg et al 2012), communication (Huber andPodos 2006), and nest building (Sheard et al 2023). Wing morphology in passerines is also associated with diet, particularly as it relates to foraging behavior and food availability (Sheard et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…Avian cranial morphology is usually associated with diet in birds, especially the beak (Soons et al 2015), though this may be constrained genetically (Bright et al 2016;Tokita et al 2017). Bird beaks are important for other functions including thermoregulation (Greenberg et al 2012), communication (Huber andPodos 2006), and nest building (Sheard et al 2023). Wing morphology in passerines is also associated with diet, particularly as it relates to foraging behavior and food availability (Sheard et al 2020).…”
Section: Discussionmentioning
confidence: 99%
“…While presumably facilitated by numerous adaptations (e.g. strong jaw and neck musculature, a hook-like beak), these traits are clearly not diagnostic of beakiation: many taxa show enlarged craniocervical muscles to support dietary specializations [78,[85][86][87][88], while beak shape has been shown to covary with numerous aspects of avian ecology [89][90][91][92][93][94][95]. Moreover, as shown by previous anecdotal reports [47] of beak suspension in spindalids-generalized Passeriformes that share few morphological traits with parrots-similar behaviours can be replicated via vastly different morphotypes.…”
Section: Broader Implicationsmentioning
confidence: 99%
“…The application of comparative methods to questions concerning variation in interspecific nest morphology has shown that a variety of factors have probably shaped nests (quite literally) from the morphology of the builders (e.g. beak shape in birds: [ 27 ]), to some of the builders' behaviours (e.g. collective foraging in ants: [ 28 ]).…”
Section: The Evolution Of Nest Building Via Comparative Analysesmentioning
confidence: 99%